Circulating micronutrient biomarkers are associated with three measures of frailty: Evidence from The Irish Longitudinal Study on Ageing (TILDA). - O'Halloran, Aisling; Kenny, Rose; Molloy, Anne; Laird, Eamon; Feeney, Joanne (My University, 2019)
Objectives: To examine the associations between 3 frailty instruments and circulating micronutrients in a large representative sample of older adults. Design: Cross-sectional data from a nationally representative cohort study conducted between October 2009 and July 2011.Participants and setting: Adults age 50 years (n¼4068) living in the community in Ireland. Measurements: Circulating micronutrients (lutein, zeaxanthin, folate, vitamin B-12, and vitamin D) were measured, transformed, and standardized. Frailty was assessed using the Frailty Phenotype, the Frailty Index, and the FRAIL Scale (fatigue, resistance, ambulation, illnesses, and loss of weight), instruments. Multinomial logistic regression determined associations between micronutrients and prefrailty or frailty. Models were adjusted for sociodemographic, lifestyle, health, and seasonal factors. Results: Adjusting for age, sex, and educational attainment, all 3 measures of frailty were associated with lower levels of lutein [relative risk ratios (RRRs): 0.43‒0.63], zeaxanthin (RRRs: 0.49‒0.63), and vitamin D (RRRs: 0.51‒0.75), and with the accumulation of micronutrient insufficiencies (RRRs: 1.42‒1.90). Attenuated but significant associations were also observed with all measures of prefrailty for lutein, vitamin D, and number of micronutrient insufficiencies. The associations with frailty persisted following additional adjustment for social, lifestyle, and health and seasonal factors, and following multiple test correction. Conclusions and implications: We have presented the most consistent evidence in the largest study to date that micronutrient concentrations are associated with prefrailty and frailty in older adults. Our data suggest that low micronutrient status has potential as an easily modifiable marker and intervention target for frailty and supports further investigation into micronutrient supplementation and fortification to prevent frailty and disability among older adults.
IN_PRESS
Keywords: Micronutrients; Biomarkers; Frailty; Aging; Ageing